Sucrose utilization and mineral nutrient uptake during hairy root growth of red beer (Beta vulgaris L.)in liquid culture - Shin, K.; Chakrabarty, D.; Ko, J.; Han, S.; Yoeup, K.
Information concerning the sugar status of plant cells is of greatimportance during all stages of the plant life cycle. The aim of this work wasto study primary carbohydrate metabolism in hairy roots of red beet. Growth ofhairy roots of red beet in vitro and changes in concentration of major nutrientsand sugar in the media were measured over a growth cycle of 16 days. We havealso determined the levels of key enzymes in the pathways of sucrose metabolism.Sucrose concentration decreased as hairy root growth proceeded while no changein glucose and fructose levels in the medium was found during the first 3 daysindicating that external sucrose is preferably taken to the cell before it ishydrolyzed by extracellular invertase. The increase in glucose and fructoselevels in the media after 5 days of culture indicates extracellular hydrolysisof sucrose which was further supported by the activity of acid invertaseobserved during that time in the culture medium. The uptake of mineral nutrientsby hairy root of red beet was monitored continuously during the culture cycle.The preferential use of NH4 + overNO3 - at the beginning of the culture andacidification of culture media were the two most notable results concerningnitrogen nutrition during hairy root growth of red beet.
Keywords: HAIRY ROOT; INVERTASE; LIQUID CULTURE; RED BEET (BETA VULGARIS); SUCROSE UTILIZATION